Pain is independently associated with reduced health related quality of life in people with psychosis. Issue 2 (15th December 2015) - Stubbs, Brendon; Gardner-Sood, Poonam; Smith, Shubulade; Ismail, Khalida; Greenwood, Kathryn; Patel, Anita; Farmer, Ross; Gaughran, Fiona
Abstract: The objective was to investigate the relationship between pain and health related quality of life (HRQOL) in people with psychosis. The study utilised a cross-sectional design including individuals with established psychosis from five Mental Health Trusts across England. Participants were classified as having pain or not and HRQOL was determined with the EQ-5D-3L. Covariates considered include the Positive and Negative Syndrome Scale (PANSS), the Montgomery Asberg Depression Rating Scale (MADRS) and Global Assessment of Functioning (GAF). Hierarchical multiple linear regression analyses were conducted. The final sample included 438 individuals with psychosis (47.5 years, SD 10.1, 193 females (42.9%)). 160 participants reported pain (36.5%) and compared to the non-pain group ( N =278) they had significantly higher depressive symptoms (MADRS 14.91 vs 8.68), total (51.8 vs 47.9) and general PANSS scores (26.8 vs. 23.5) and lower overall HRQOL (54.7 vs 68.3). The final regression analysis ( n =387) demonstrated that lower levels of pain were a predictor of better HRQOL ( β =.173) after adjusting for the PANSS, MADRS and GAF. Depressive symptoms were the largest predictor of HRQOL ( β =−.486). Only 1–2% of the sample were in receipt of analgesic medication suggesting pain is greatly overlooked despite its wider deleterious impact on HRQOL. Highlights: One third of participants with psychosis experience clinically relevant pain. People with psychosis pain experience higher levels of depressive symptoms. Pain appears to be associated with worse quality of life in people with psychosis. Only 1–2% of participants were receiving analgesic medication, indicating pain is overlooked.